Effectiveness of Online Mediation in Resolving Cross-Border Civil Disputes - Shohib Muslim; Bouyea Jonathan; Uwe Barroso; Anna Rahma Syam (Yayasan Adra Karima Hubbi, 2024)
Background: The rapid advancement of digital technologies has transformed various aspects of the legal field, including dispute resolution. Online mediation has emerged as a promising method for resolving cross-border civil disputes, offering a convenient and cost-effective alternative to traditional litigation. Despite its potential, the effectiveness of online mediation in this context remains underexplored, particularly in terms of user satisfaction, cost savings, and resolution time. Objective: This study aims to evaluate the effectiveness of online mediation in resolving cross-border civil disputes. The research seeks to assess user satisfaction, cost efficiency, and the duration of the mediation process compared to traditional methods. The goal is to provide empirical evidence on the viability of online mediation as a dispute resolution mechanism in international contexts. Methods: A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 200 participants who have engaged in online mediation for cross-border disputes, measuring their satisfaction, cost savings, and resolution time. Qualitative interviews with 30 mediators provided deeper insights into the challenges and advantages of online mediation. The data were analyzed using statistical methods for the surveys and thematic analysis for the interviews. Results: Findings indicate that online mediation is highly effective in resolving cross-border civil disputes, with 85% of participants expressing satisfaction with the process. Cost savings averaged 40% compared to traditional litigation, and the average resolution time was reduced by 50%. Mediators highlighted the flexibility, accessibility, and reduced logistical challenges as significant advantages of online mediation. Conclusion: Online mediation is an effective method for resolving cross-border civil disputes, offering high user satisfaction, significant cost savings, and reduced resolution times. Implementing best practices can further optimize these benefits. Future research should explore the long-term impacts and develop strategies to address identified challenges, ensuring the sustainable integration of online mediation in international dispute resolution.